Preparing young adolescents for a bright future—right now!. Issue 1 (1st January 2016) - Deering, Paul D.; Martin, Kathryn L.; Buelow, Stephanie M.; Hoffman, Jennifer T.; Cameli, Sandy; Martin, Matt; Walker, Robert E.; O'Neill, Tara B.
Abstract: We must prepare young adolescents for a bright future by examining all of our educational practices in terms of their current and future relevance. The education we provide our students must prepare them to address enormously complex issues involving demographics and international relations, environmental and human health, and the development and application of technology. This We Believe 's (NMSA, 2010) essential attributes of successful schooling can light the way to a bright future. We have clustered the 16 attributes around Four C's: constructivism, collaboration, caring, and comprehensive education. A fifth "C" that weaves through all of the others is critical thinking. The authors and their young adolescent students offer examples of these principles in action, some which may seem "old school" and some "futuristic." However, all can empower our young adolescents to thrive today as well as in a bright future of their making.